The contribution of smoking and smokeless tobacco to oesophageal squamous cell carcinoma risk in the African oesophageal cancer corridor: Results from the ESCCAPE multicentre case‐control studies. Issue 11 (21st February 2023) - Simba, Hannah; Menya, Diana; Mmbaga, Blandina T.; Dzamalala, Charles; Finch, Peter; Mlombe, Yohannie; Mremi, Alex; Narh, Clement T.; Schüz, Joachim; McCormack, Valerie
Abstract: Tobacco use is a well‐established risk factor for oesophageal squamous cell carcinoma (ESCC) but the extent of its contribution to the disease burden in the African oesophageal cancer corridor has not been comprehensively elucidated, including by type of tobacco use. We investigated the contribution of tobacco use (smoking and smokeless) to ESCC in Tanzania, Malawi and Kenya. Hospital‐based ESCC case‐control studies were conducted in the three countries. Incident cases and controls were interviewed using a comprehensive questionnaire which included questions on tobacco smoking and smokeless tobacco use. Logistic regression models were used to estimate odds ratios (OR) and their 95% confidence intervals (CI) of ESCC associated with tobacco, adjusted for age, sex, alcohol use, religion, education and area of residence. One thousand two hundred seventy‐nine cases and 1345 controls were recruited between August 5, 2013, and May 24, 2020. Ever‐tobacco use was associated with increased ESCC risk in all countries: Tanzania (OR 3.09, 95%CI 1.83‐5.23), and in Malawi (OR 2.45, 95%CI 1.80‐3.33) and lesser in Kenya (OR 1.37, 95%CI 0.94‐2.00). Exclusive smokeless tobacco use was positively associated with ESCC risk, in Tanzania, Malawi and Kenya combined (OR 1.92, 95%CI 1.26‐2.92). ESCC risk increased with tobacco smoking intensity and duration of smoking. Tobacco use is an important risk factor of ESCC in Tanzania, Malawi and Kenya. Our study provides evidence that smoking and smokeless tobacco cessation are imperative in reducing ESCC risk. Abstract : What's new? Oesophageal squamous cell carcinoma (ESCC) is the most common histological subtype of oesophageal cancer in the eastern to southern corridor of Africa. Nonetheless, data on tobacco use and ESCC risk in Africa is lacking. Here, using a comprehensive questionnaire, the authors evaluated the impact of smoking and smokeless tobacco use on ESCC risk in Tanzania, Malawi and Kenya. Smoking and smokeless tobacco use were positively associated with ESCC risk. Prevalence of tobacco use was highest among men and among those in rural areas and with lower education. The findings provide critical insight for interventions and tobacco cessation programmes in Africa.